Obowiązek dokonania racjonalnych usprawnień – uwagi na tle wyroku TSUE Jetta Ring i Lone Skouboe Werge (C-335/11 I C-337/11): [The duty to provide reasonable accommodation - reflections on the CJEU judgment in Jetta Ring and Lone Skouboe Werge (C-335/11 AND C-337/11)] (Studia Prawnicze / The Legal Studies, 2013)
11 kwietnia 2013 r. Trybunał Sprawiedliwości Unii Europejskiej (dalej: TSUE) wydał długo oczekiwany wyrok w sprawie wykładni przepisów Dyrektywy 2000/78/WE1 w zakresie defi nicji pojęcia „niepełnosprawność” oraz obowiązku stosowania „racjonalnych usprawnień”. Wniosek o wydanie orzeczenia w trybie prejudycjalnym skierował duński sąd (Sø- og Handelsretten) w związku z powództwem dwóch kobiet, które zostały zwolnione z pracy z powodu nieobecności spowodowanej leczeniem urazów kręgosłupa. Tym samym TSUE dokonał kolejnej ewolucji standardu ochrony osób niepełnosprawnych w prawie UE, gdyż ani poprzednie orzeczenia w tej materii, ani ratyfi kowana przez Unię Europejską Konwencja ONZ o Prawach Osób z Niepełnosprawnością nie wyjaśniały różnicy między niepełnosprawnością a chorobą. The Article posits that in Jetta Ring and Lone Skouboe Werge (C-335/11 and C-337/11) the CJEU has contributed to further evolution of the protection of persons with disabilities under the EU law and clarified the important difference between disability and illness. Following the UN Convention on Rights of Persons with Disabilities, as ratified by the EU in 2010, it held that disability covers a condition caused by a curable or incurable illness, which entails a longterm limitation in the full and effective participation in professional life on an equal basis with other workers. The limitation as such results from the interaction of human impairments with social barriers. Therefore, the termination of employment due to the employee’s absence from work because of illness may constitute unlawful discrimination based on disability if the employer failed to provide the employee with reasonable accommodation in pursuance to Article 5 of the Framework Directive 2000/78/EC. The Article argues that significant differences in national laws implementing the relevant provisions of the Framework Directive lead to an unequal protection of the disabled across the EU. Drawing the comparison with Americans with Disabilities Act the Article identifies the best practical examples of providing reasonable accommodation which give full effect to the ratio of this legislation.